2017
DOI: 10.1186/s13068-017-0778-0
|View full text |Cite
|
Sign up to set email alerts
|

Regional water footprints of potential biofuel production in China

Abstract: BackgroundDevelopment of biofuels is considered as one of the important ways to replace conventional fossil energy and mitigate climate change. However, rapid increase of biofuel production could cause other environmental concerns in China such as water stress. This study is intended to evaluate the life-cycle water footprints (WF) of biofuels derived from several potential non-edible feedstocks including cassava, sweet sorghum, and Jatropha curcas in China. Different water footprint types including blue water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 65 publications
1
12
0
1
Order By: Relevance
“…However, any areas shown in white are considered least suitable with slope amount more than 30°. Surface slopes greater than 30 degrees directly influence the soil erosion, sediments transportation, irrigation and drainage patterns 23 . A land with slope greater than 25 or 30 degrees is usually given the least priority as it is a cause of water loss and soil erosion.…”
Section: Resultsmentioning
confidence: 99%
“…However, any areas shown in white are considered least suitable with slope amount more than 30°. Surface slopes greater than 30 degrees directly influence the soil erosion, sediments transportation, irrigation and drainage patterns 23 . A land with slope greater than 25 or 30 degrees is usually given the least priority as it is a cause of water loss and soil erosion.…”
Section: Resultsmentioning
confidence: 99%
“…The life cycle of sweet sorghum-based ethanol includes five stages: sweet sorghum planting and harvesting stage, sweet sorghum transport stage, ethanol production stage, ethanol transport and distribution stage, and ethanol combustion stage. The water consumption of every life cycle stage was analyzed, except for the two transport stages and the ethanol combustion stage because the quantity of water consumption in these three stages represented less than 1% of the total water consumption [16,17]. The GHG emissions and net energy gain were assessed by tracking the material and energy flow in all stages.…”
Section: System Boundary Definitionmentioning
confidence: 99%
“…Recent studies showed that inappropriate development planning of biofuels may cause conflicts with water and food [14]. Increased biofuel demand would push up water use, and the low water efficiency of developing bio-ethanol on the marginal lands could aggravate water consumption [15][16][17]. Besides, planting energy crops on the cultivated lands may improve energy supply, but it also results in less cultivated lands for food planting and causes risks to food security [18].…”
Section: Introductionmentioning
confidence: 99%
“…They defined the WF of a product as the total volume of fresh water consumed across the entire value chain of production. Previous studies of WF have investigated the water footprints of ethanol production [19][20][21][22][23] but most of them focused on calculating the WFs of feedstocks; few have reported the WF at an industrial scale. In this study, the WF of ethanol production on an industrial scale was calculated and used as an evaluation indicator for water integration.…”
Section: Introductionmentioning
confidence: 99%